Surveillance Cultures and Infection in 230 Pacemaker and Defibrillator Generator Changes in Pediatric and Adult Congenital Patients. Issue 3 (May 2021) - Webster, Gregory; Balmert, Lauren C.; Patel, Ami B.; Kociolek, Larry K.; Gevitz, Melanie; Olson, Rachael; Chaouki, Ahmed S.; El-Tayeb, Osama; Monge, Michael C.; Backer, Carl
Background: Postoperative infections can occur during surgical replacement of pulse generators for pacemakers and implantable cardioverter-defibrillators. The incidence of infection is poorly documented in children and patients with adult congenital heart disease. The utility of surveillance cultures obtained from device pocket swabs is unknown in this group. Methods: We reviewed surgical replacements of cardiovascular implantable pulse generators from 2010 to 2017. Two cohorts were defined. In a surveillance cohort (123 patients), aerobic and anaerobic culture swabs of the device pocket were obtained at the time of generator change. In a nonsurveillance cohort (107 patients), generator change occurred without obtaining cultures. Results: During 230 generator changes (mean patient age 19 years; 77% with structural congenital heart disease), two clinical infections occurred at the surgical site (0.9% incidence). Neither infection occurred in the surveillance cohort. Cultures were positive in 12 (9.8%) of 123 patients in the surveillance cohort, but 11 of 12 were likely contaminants and none were subsequently associated with clinical disease. There was no association between clinical infection or positive surveillance cultures and the location of pulse generator, the presence of other concurrent surgeries, or a history of prior pocket infection. Conclusions: Clinical infection was rare after pulse generator change in children and young adults. No cases required reintervention on the pocket. Surveillance cultures did not improve clinical care. These data extend current recommendations that surveillance cultures are not required during generator change to the pediatric and young adult population.